Les élections législatives de mars 1978 et la politique extérieure de la France - Merle, Marcel (Études internationales, 1978)
The international aspect of electoral consultations is too often neglected by researchers. In the specific case of France, observation shows that international stakes have already played an important role in other circumstances (notably in 1973). In 1978, the confrontation opposing the majority in power and the leftist opposition was played out, in part, on international problems. The defeat of the left has certainly multiple causes ; but the rupture which weakened the opposition occurred, initially, because of questions of foreign policy ; as for the incumbent majority, it found in the continuity of foreign policy its best arguments with public opinion. Just as foreign policy was able to contribute, in a certain way, to electoral results, the latter could have a certain influence on the course of French foreign policy. This case study suggests the need for further comparative research in order to draw up a typology of electoral consultations, according to whether or not they involve an external stake, but also to define more precisely the ambiguous concept of foreign policy — which may not be reduced, as the French electoral campaign of 1978 proves, to problems of alliances and defense only.